Doctrinal and Comparative Assessment of GMO Liability Laws in the UAE - Dina Imad; Maya Khater; Nagwa Abouhaiba; Enas Qutieshat; Ali AlMatrooshi (Contrarius Indonesia, 2026)
Genetically modified organisms (GMOs) have become an integral part of modern biotechnology. However, their increasing use has sparked complex debates. The controversy pertains to balancing the benefits of biotechnological improvements against potential risks to biodiversity and public health. The current study aims to critically evaluate the legal texts related to accountability and civil liability for damages caused by GMOs. It seeks to assess the adequacy of UAE legislation in establishing effective mechanisms for liability and compensation for environmental and health impacts, thus answering the central question to what extent does the current UAE law enhance accountability compared to international standards. It employs a descriptive-analytical and comparative legal approach based on the analysis and critique of relevant international and UAE legal documents. The findings reveal that the UAE has established an advanced regulatory system aligned with international standards; however, significant legal gaps remain in definitional clarity, sanctions framework, liability rules, and enforcement provisions. The study concludes with a synthesis table and figure mapping points of convergence and difference between national and international instruments. The study recommends further development of the rules related to compensation and penalties to ensure appropriate legal deterrence for GMO-related harm and calls for legislative amendments that enhance the clarity of texts and their integration with international frameworks.